Equine atypical myopathy: A metabolic study. (October 2016) - Karlíková, R.; Široká, J.; Jahn, P.; Friedecký, D.; Gardlo, A.; Janečková, H.; Hrdinová, F.; Drábková, Z.; Adam, T.
Highlights: Equine atypical myopathy by a metabolic approach. Changes in metabolic profile reflect the progress of the disease. Alterations in the metabolism of fatty, amino and organic acids, purines, pyrimidines and vitamins. Graphical Abstract: Abstract: Atypical myopathy (AM) is a potentially fatal disease of grazing horses. It is reportedly caused by the ingestion of sycamore seeds containing toxic hypoglycin A. In order to study metabolic changes, serum and urine samples from nine horses with atypical myopathy and 12 control samples from clinically healthy horses were collected and then analysed using a high-performance liquid chromatography coupled with tandem mass spectrometry; serum metabolic profiles as the disease progressed were also studied. Metabolic data were evaluated using unsupervised and supervised multivariate analyses. Significant differences were demonstrated in the concentrations of various glycine conjugates and acylcarnitines (C2–C26). Moreover, the concentrations of purine and pyrimidine metabolites, vitamins and their degradation products (riboflavin, trigonelline, pyridoxate, pantothenate), and selected organic and amino acids (aspartate, leucine, 2-oxoglutarate, etc.) were altered in horses with AM. These results represent a global view of altered metabolism in horses with atypical myopathy.